2007
DOI: 10.1590/s1519-69842007000500012
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evidence of population structuring in the neotropical freshwater fish Brycon hilarii (Valenciennes, 1850)

Abstract: Brycon hilarii is a migratory fish widely distributed throughout the Paraguay River Basin. It is appreciated in sport fishing and for its superior meat quality. It is also the main species for tourist attraction in the Bonito region (State of Mato Grosso do Sul, Brazil). Considering the lack of information on the genetic structure of the fish of this species, the aim of the present study was to detect the genetic variability of Brycon hilarii through RAPD markers. A total of eighty specimens collected in diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 21 publications
5
21
0
1
Order By: Relevance
“…Population structuring has also been found in B. hilarii from the Paraguay River Basin (Sanches & Galetti, 2007). Significant genetic differences were detected between populations and the authors assumed that the spawning schools may organize themselves in such way as to maintain the integrity of each subunit residing in the system.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Population structuring has also been found in B. hilarii from the Paraguay River Basin (Sanches & Galetti, 2007). Significant genetic differences were detected between populations and the authors assumed that the spawning schools may organize themselves in such way as to maintain the integrity of each subunit residing in the system.…”
Section: Discussionmentioning
confidence: 96%
“…In recent years, the number of genetic studies on Neotropical freshwater fish have indicated structuring of their populations within a same hydrographic basin (for a review, see Piorski et al, 2008), including migratory species (Machado et al, 2005;Sanches & Galetti, 2007). The present study revealed different results for both migratory fish species studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sanches & Galetti Jr. (2007) used RAPDs to assess the genetic variability of 80 individuals of the migratory characin Brycon hilarii at four sites of the rio Miranda subbasin (Paraná-Paraguay basin) and found significant population differences. Those differences, however, were more evident during the dry season when fish movement is limited.…”
Section: Conservation Issuementioning
confidence: 99%